أثر الربيع العربي على الإصلاح السياسي في الأردن - حنتولي، إيمان عبدالعزيز فهيم (مركز البحث وتطوير الموارد البشرية - رماح, 2019)
هدفت الدراسة إلى تتبع واقع الربيع العربي، وتأثيره على عملية الإصلاح السياسي في الأردن، وإبراز أهم مضامين الإصلاح السياسي التي قام بها النظام السياسي الأردني بعد العام ۲۰۱۱، وإظهار التحديات والمعوقات التي تواجه عمليات الإصلاح السياسي في الأردن. وقد وظفت الدراسة منهج تحليل النظم للإجابة عن فرضيتها القائلة بوجود علاقة ارتباطية بين الربيع العربي وبين عمليات الإصلاح السياسي في الأردن، إذ تبين للدراسة أن تلك العلاقة الارتباطية كانت موجبة، من خلال تعديل ثلثي الدستور الأردني، وصدور عدة قوانين معدلة وجديدة تنظم العمل السياسي، وتساهم في توسيع قاعدة المشاركة الشعبية في صنع القرار، وتطوير بنى وهياكل جديدة في الأردن مثل الهيئة المستقلة للانتخابات، والمحكمة الدستورية. وقد وجدت الدراسة أن التأطير القانوني للإصلاح السياسي في الأردن متوفر، ولكن لا تزال هناك إشكالية في التطبيق بسبب مجموعة من العوامل، من أهمها: قوى الشد العكسي، وغياب دور المعارضة السياسية، وضعف الأحزاب السياسية ومؤسسات المجتمع المدني من حيث التعبئة السياسية والتجنيد السياسي، ونمط الثقافة السياسية السائدة في المجتمع الأردني. كما وجدت الدراسة أن استجابة النظام السياسي الأردني لبعض مطالب الحراكيين والتعامل معهم بسلمية في الأردن خلال الفترة ۲۰۱۱- ۲۰۱۷، إذ تميز الحراك ساهمت بشكل كبير في تحقيق الاستقرار السياسي الأردني عن غيره من الحراكات في الدول العربية بأنه لم يطالب بإسقاط النظام، وإنما طالب بالإصلاحات وزيادة المشاركة السياسية، أضف إلى ذلك رسوخ القناعة لدى صانع القرار الأردني بأهمية الإصلاح وتعزيز الديمقراطية كنهج حياة وزيادة المشاركة السياسية لتشمل كافة فئات المجتمع الأردني. وفي ضوء النتائج التي توصلت إليها الدراسة، تم اقتراح مجموعة من التوصيات، منها: رفع درجات الوعي السياسي لدى المواطنين من أجل بناء ثقافة سياسية تقود لمزيد من المشاركة السياسية، وإعادة النظر في قانون الانتخاب، والاستعانة بوسائل الإعلام المختلفة لتغيير الصورة النمطية للمرأة، وتسليط الضوء على النساء كمواطنات فاعلات. The study aimed to follow the reality of the Arab Spring and its impact on the process of political reform in Jordan, and highlight the most important contents of the political reform carried out by the Jordanian political system after 2011, and to show the challenges and obstacles facing the political reform processes in Jordan. The study used the systems analysis approach to answer its hypothesis that there is a correlation between the Arab Spring and the political reform processes in Jordan. The study found that this relationship was positive through the amendment of two-thirds of the Jordanian constitution, the promulgation of several new and amended laws regulating political action, and the expansion of popular participation in decision-making and the development of new structures and structures in Jordan such as the Independent Electoral Commission and the Constitutional Court. The study found that the legal framework for political reform in Jordan is available, but there is still a problem in implementation due to a number of factors, the most important of which are: The absence of the role of political opposition, the weakness of political parties and civil society institutions in terms of political mobilization and political recruitment, and the pattern of political culture prevalent in Jordanian society. The study also found that the response of the Jordanian political system to some of the demands of the movement and dealing with them peacefully contributed significantly to the political stability in Jordan during the period 2011-2017. The Jordanian movement distinguished from other movements in the Arab countries that it did not demand the overthrow of the regime, but to increase political participation. In addition, Jordanian policymakers are convinced of the importance of reform and the promotion of democracy as a way of life and increase political participation to all sectors of Jordanian society. In light of the findings of the study, a number of recommendations were proposed, including: raising political awareness among citizens in order to build a political culture leading to greater political participation, reconsidering the election law, and using various media to change the stereotype of women, and highlighting women as active citizens.
Keywords: الثورات العربية -- الأنظمة السياسية -- الإصلاحات السياسية -- الاستقرار السياسي -- الأردن